2000
DOI: 10.1002/abio.370200207
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crude oil contamination on the bacterial community of semiarid soils of Patagonia (Argentina)

Abstract: Autochthonous bacteriocenoses in semiarid soils in Patagonia were found to be capable of rapidly adapting to high contamination with crude oil. This adaptation at community level is due to the selective enrichment of hydrocarbon-utilizing bacteria always present in these soils. Immediately after a heavy contamination with crude oil, the autochthonous bacteriocenosis contained about 28% hydrocarbon-utilizing bacteria which could be classified into eight ecotypes with characteristic metabolic profiles. Mainly n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 35 publications
(21 reference statements)
7
30
0
1
Order By: Relevance
“…Although P. stutzeri was one of the first alkane-degrading microorganisms identified-it was identified as Bacterium stutzeri (333)-few reports of crude oil-, oil derivative-, and/or aliphatic hydrocarbon-degrading P. stutzeri strains have appeared in the literature (81,95,156,163,166,268). In contrast, much information is available for other Pseudomonas species, such as P. aeruginosa, P. fluorescens, P. oleovorans, and P. putida (reviewed in reference 365).…”
Section: Biodegradation and Useful Properties For Biotechnological Apmentioning
confidence: 99%
“…Although P. stutzeri was one of the first alkane-degrading microorganisms identified-it was identified as Bacterium stutzeri (333)-few reports of crude oil-, oil derivative-, and/or aliphatic hydrocarbon-degrading P. stutzeri strains have appeared in the literature (81,95,156,163,166,268). In contrast, much information is available for other Pseudomonas species, such as P. aeruginosa, P. fluorescens, P. oleovorans, and P. putida (reviewed in reference 365).…”
Section: Biodegradation and Useful Properties For Biotechnological Apmentioning
confidence: 99%
“…(33), are also known to have high desiccation tolerance (11). Actinomycetes are an abundant bacterial group in soil, with a critical role in the decomposition of organic matter.…”
mentioning
confidence: 99%
“…The isolation and characterization of N. globerula strain 432 were done in a previous study [4]. The strain was isolated from a soil sample collected in east Patagonia (Argentina).…”
Section: Bacterial Strain Media and Growth Conditionsmentioning
confidence: 99%
“…The composition of the phenyldecane-derived intermediates indicated that the hydrocarbon was metabolized by L-oxidation and, to some extent, K-oxidation of the aliphatic side chain. The conversion of hydrocarbons into storage lipids during N-starvation is an interesting feature of these bacteria since these conditions are usually found in soil environments [4]. Moreover, these microorganisms have a broad metabolic spectrum for the transformation and degradation of di¡erent kinds of substrates, including a variety of alkanes, halogenated aliphatics and aromatics and other xenobiotic pollutants [5,6].…”
Section: Introductionmentioning
confidence: 99%